Real exchange rate dynamics in New-Keynesian models – The Balassa-Samuelson effect revisited - Maren Brede (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper explores the Balassa-Samuelson effect in a New-Keynesian DSGE model of a monetary union with traded and non-traded goods. Credible sets for theoretical impulse response functions show that a model with perfect intersectoral labour mobility is unable to reproduce an appreciation of the real exchange rate caused by higher productivity in the traded sector. Allowing for imperfect intersectoral labour mobility resolves this obstacle and delivers testable restrictions for model parameters governing the labour market specification in a Bayesian estimation context.
Keywords: F41; F45; F47; C51; 330; Real exchange rate; Balassa-Samuelson; prior predictive analysis